Analysis Of The Financial Performance Of Pt Bank Rakyat Indonesia (PERSERO) TBK For The 2012-2021 Period - Jufri, Achmad; Arifina, Mufti; Darmawan, Darmawan (JEKP (Jurnal Ekonomi dan Keuangan Publik), 2023)
This analysis aims to determine the performance effectiveness of PT Bank Rakyat Indonesia (Persero) Tbk 2012-2021. This analysis uses descriptive quantitative research methods, in this case using several financial ratios: liquidity, activity, probability, solvency, and working capital. The study was carried out from 2012 to 2021. Based on this analysis, the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk in terms of liquidity ratios is quite good because the company can pay debts at maturity. The solvability ratio is in good condition because the company has increased yearly in fulfilling all of its obligations. Meanwhile, the activity ratio of the company's financial performance worsened/poorly.